Violation of the Obligation to Use Indonesian Language in International Business Contracts Involving Foreign Legal Entities as Parties under Indonesian Law - Sonyendah Retnaningsih; Muhammad Rizqi Alfarizi Ramadhan; Supaphorn Akkapin (PT. Multidisciplinary Press Indonesia, 2024)
The Indonesian language is the official national language, required for use in all official state documents in Indonesia, as stated in Law No. 24 of 2009 on the National Flag, Language, Emblem, and Anthem. Article 31, paragraph (1) mandates the use of Indonesian in memorandums of understanding (MoUs) or agreements between state organizations, Indonesian government agencies, and private entities. When a foreign party is involved, Article 31, paragraph (2) requires the agreement to be in both Indonesian and the foreign language or English. Presidential Regulation No. 63 of 2019 also emphasizes the use of Indonesian in agreements, allowing foreign languages only as translations to ensure mutual understanding. However, the Supreme Court Circular Letter No. 3 of 2023 complicates this by stating that Indonesian private institutions or individuals cannot cancel agreements made in a foreign language without an Indonesian translation, unless bad faith is proven. This creates inconsistency with the regulations. This research examines two main issues: first, the synchronization of regulations regarding the use of Indonesian in agreements with foreign parties, and second, the legal consequences of agreements that do not use Indonesian. The research uses doctrinal and descriptive methods, with qualitative analysis of secondary data, concluding that agreements not in Indonesian are legally void and may be annulled by the courts.